2020
DOI: 10.3390/genes11111380
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Information Recovery from Human Stool Samples Is Influenced by Sequencing Depth and Profiling Method

Abstract: Sequencing of the 16S rRNA gene (16S) has long been a go-to method for microbiome characterization due to its accessibility and lower cost compared to shotgun metagenomic sequencing (SMS). However, 16S sequencing rarely provides species-level resolution and cannot provide direct assessment of other taxa (e.g., viruses and fungi) or functional gene content. Shallow shotgun metagenomic sequencing (SSMS) has emerged as an approach to bridge the gap between 16S sequencing and deep metagenomic sequencing. SSMS is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…As the children aged, Microviridae--primarily Gokoshuviruses and poophages-became the dominant phages in the gut (Liang et al, 2020; Lim et al, 2020; Takahashi et al, 2000). While little is known about the recently identified poophages (Santiago-Rodriguez et al, 2020), the Gokushoviruses have been recently described (Creasy et al, 2018; Székely and Breitbart, 2016; Kirchberger & Ochman, 2020). These phages were initially only identified in Bdellovibrio and Chlamydophila bacteria but have now been identified in Escherichia coli , surviving in the cytoplasm (Kirchberger & Ochman, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As the children aged, Microviridae--primarily Gokoshuviruses and poophages-became the dominant phages in the gut (Liang et al, 2020; Lim et al, 2020; Takahashi et al, 2000). While little is known about the recently identified poophages (Santiago-Rodriguez et al, 2020), the Gokushoviruses have been recently described (Creasy et al, 2018; Székely and Breitbart, 2016; Kirchberger & Ochman, 2020). These phages were initially only identified in Bdellovibrio and Chlamydophila bacteria but have now been identified in Escherichia coli , surviving in the cytoplasm (Kirchberger & Ochman, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous works suggest that species level taxonomic profiles obtained by mapping reads on reference genomes were highly similar to deep WGS, and that the resulting α-diversity metrics were barely impacted by limiting the sequencing depth to ∼ 500K − 1M reads/sample [12] [15] [16] [17]. Furthermore, mapping on reference genomes was more efficient than on a marker genes catalog in the context of SSM [15]. By contrast, the depth required for functional analysis depends on the level of granularity of the analysis: 500K reads/sample may be sufficient to identify KEGG orthology groups [12], but 3M to 5M reads/sample are necessary to accurately detect genes and pathways [15] [18], and very deep sequencing up to ∼ 60 − 80M reads/sample is needed to study antimicrobial resistance genes [16] [19].…”
Section: Introductionmentioning
confidence: 99%
“…The shallow metagenomic sequencing (SMS) strategy has been preferred to the 16S rRNA gene amplicon strategy in certain microbiome studies (Zhu et al, 2021). The use of the SMS strategy may decrease the costs associated with metagenomic sequencing strategy (Hillmann et al, 2018;Santiago-Rodriguez et al, 2020). A comparative analysis of infant gut microbiota indicated that 16S rRNA gene amplicon and metagenomic sequencing approaches can provide similar alpha and beta diversity of the gut microbiota (Peterson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%